Increase use of contact lenses for optical correction - Paudel, P.; Khadka, J.; Sharma, A.K.; Shakya, S.; Shrestha, J.K.; Shah, D.N. (Journal of Institute of Medicine Nepal, 2007)
Introduction: Contact lenses (CL) are considered as a widely accepted modality of refractive correction in the last few decades, though their history is nearly about 100 years old. Millions of people are wearing contact lenses all over the world. Every year the number of CL wearers has increased significantly. No definite statistics are available regarding the number of people wearing contact lenses in Nepal. Contact lenses are not used only for refractive correction but also for therapeutic and cosmetic use.1 Methodology: The main purpose of the study was to find the popularity of contact lenses irrespective to other optical correction. A hospital based retrospective study was conducted evaluating the medical records of 848 CL patients attended in CL clinic at B. P. Koirala Lions Centre for Ophthalmic Studies. Results: In this study, the number of CL wearers was found to increase significantly every year. The number of contact lens wearers in the year 2002-2003 was 158 where as in the later years the number reached up to 326 and 364 respectively. Similarly, the numbers of RGP wearers and bandage CL wearers also increased significantly in comparison to previous years. Almost 90 percent wearers were using soft contact lens. It was found to be more popular among the age group of 21yrs to 30 yrs. The number of female wearers was predominant than the male wearers. The contact lens wear ocular complications were found to be very rare. Conclusion: In Nepal, contact lenses are being considered as suitable alternatives for optical correction due to better cosmesis than the conventional mode of optical correction. Journal of Institute of Medicine Vol.28(1) 2006